MODIFICATION OF SCREEN PRINTED CARBON ELECTRODEBY POLYPYRROLE FOR DETERMINATION OF HYDROQUINONE - Khoirul Ngibad; Ani Mulyasuryani; Diah Mardiana (Alchemy)
Electropolymerization of polypyrrole for determination of hydroquinone on screen printed carbon electrode (SPCE) was performed using cyclic voltammetry. Electropolymerization of polypyrrole on SPCE begins with determining the optimum conditions of cyclic voltammetry (working potential, scan rate, number of cycles) and the conditions of solution (pyrrole and KCl concentrations).The working potential were varied at 0 – 0.8; 0 – 0.9; 0 – 1 V. The variation of scan rate were 50, 100, 150 mV/s and number of cycleswere 5, 10,15 cycles. The influence of pyrrole concentration was studied by providing variation of 5, 50, 100 mM. Meanwhile, the KCl concentration were at 0.1; 0.5; 1 M. The SPCE modified with polypyrrole was washed with deionized water and was dried at room temperature. The prepared polypyrrole was analyzed and based on the high anodic and cathodic peak current of the hydroquinone, it is confirmed that the preparation was succefully conducted. The optimum conditions on electropolymerization of polypyrrole areat the working potential of 0 – 0.9 V; the scan rate 100 of mV/s; the number of cyclesis 10, and at thepyrroleconcentration of 50 mM and KCl concentration of 0.5 M. SPCE modified polypyrrole can determine the hydroquinone at the concentration range of 5 – 100 μM with the sensitivity of 0.120 μA/Μm and the detection limit (S/N = 3) of 0.8 μM.